La valorisation de la recherche : une nouvelle mission pour l’université? - Mailhot, Chantale; Pelletier, Patrick; Schaeffer, Véronique (Canadian Journal of Higher Education, 2007)
Over the last few years the process of adding value to academic research results has become a growing phenomenon entailing important institutional changes. In the context of the knowledge economy, universities are considered to be central socio-economic actors. They are concerned with the development and the organization of technology transfer and the management of intellectual property. However, the value-adding process runs the risk of becoming confined to the commercialization of research results. The evolution of the role of the university in the economy and society is a subject of debates among politicians as well as academic and industrial actors. What is the impact of the process of adding value to research, considered as a new mission of the university, on the changing academic environment and on the traditional role of the university? To study this question we focus on the cases of Canada and Quebec.